Effects of Washing on the Functional Properties of Duck Meat - Ismail, Ishamri; Huda, Nurul; Ariffin, Fazilah; Ismail, Noryati (International Journal of Poultry Science, 2010)
The objective of this research was to study the effect of washing cycles on the functional properties of washed duck meat. Five types of treatment were applied in this study: unwashing, single, double, triple and quadruple washing. The washing cycles were found to reduce fat content and protein content significantly. The quadruple washing resulted in the lowest cholesterol and myoglobin contents. Double washing showed significantly higher Lightness (L*) and Whiteness (W) values than the other washing cycles. Washing cycles increased the shear force of the samples (p>0.05). Washing cycles also significantly affected pH, folding test, gel strength, expressible moisture and WHC; quadruple washing exhibited a significantly higher pH, folding score, expressible moisture and WHC but reduced the gel strength of the sample. Sample treated with a double washing cycle exhibited the highest folding score, a low fat content and the best lightness and whiteness values.